Selection for overhead concealment improves nest survival of a ground nesting bird in Argentinian rangelands - Colombo, Martín Alejandro (2024)
Grassland ecosystems have suffered intense modification worldwide, resulting in a loss of biodiversity. Birds that breed in grasslands have experienced steep population declines over recent decades. When modifications of grasslands reduce the available breeding habitat, birds may select habitat features that do not favor their breeding success. However, the relationship between selected nesting habitat and nest survival is not well established for many grassland birds. We studied the nest site selection and nest survival of a common grassland bird, the Grassland Yellow-Finch Sicalis luteola, in the Flooding Pampa of Argentina, a region comprised mostly of large natural rangelands. We searched for nests over three breeding seasons (2017–2020) and used linear models to analyze whether finches selected nest sites according to distance from grassland edges, type of grassland community, vegetation density, visual concealment, and grass height. We modeled daily nest survival rates (DSR) to assess whether these variables influenced breeding success. We confirmed the fate of 133 nests, of which 93 (70%) failed, predation being the principal cause (84% of failures). Our models showed that finches selected shrubby grasslands over other types available, and sites with high overhead visual concealment. Only overhead concealment was positively correlated with DSR. This may indicate that their nests are affected by avian predators that search for prey from above and that they benefit from tall and dense vegetation that provides good overhead cover. We believe that preserving areas of heterogeneous and dense shrubby grasslands within grazing plots is a good starting point that could benefit this bird species and others with similar nesting strategies.